2020
DOI: 10.1186/s13024-020-00386-4
|View full text |Cite
|
Sign up to set email alerts
|

Impaired NHEJ repair in amyotrophic lateral sclerosis is associated with TDP-43 mutations

Abstract: Background Pathological forms of TAR DNA-binding protein 43 (TDP-43) are present in motor neurons of almost all amyotrophic lateral sclerosis (ALS) patients, and mutations in TDP-43 are also present in ALS. Loss and gain of TDP-43 functions are implicated in pathogenesis, but the mechanisms are unclear. While the RNA functions of TDP-43 have been widely investigated, its DNA binding roles remain unclear. However, recent studies have implicated a role for TDP-43 in the DNA damage response. Methods We used NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(117 citation statements)
references
References 79 publications
9
103
0
Order By: Relevance
“…We show that MDMi from ALS patients displayed increased γH2AX foci and pan-nuclear γH2AX phosphorylation in ALS MDMi compared to HC MDMi under basal conditions. This result is in line with other reports showing that ALS tissues exhibit increased DNA damage foci, likely mediated by oxidative and replication stress, as recently substantiated in studies of different ALS cell models (Konopka et al, 2020; Mitra et al, 2019; Riancho et al, 2020). Although it has been shown that TDP-43 is recruited less efficiently to DNA damage foci leading to unresolved DDR (Mitra et al, 2019), further studies are needed to examine DDR signalling pathways in ALS MDMi.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We show that MDMi from ALS patients displayed increased γH2AX foci and pan-nuclear γH2AX phosphorylation in ALS MDMi compared to HC MDMi under basal conditions. This result is in line with other reports showing that ALS tissues exhibit increased DNA damage foci, likely mediated by oxidative and replication stress, as recently substantiated in studies of different ALS cell models (Konopka et al, 2020; Mitra et al, 2019; Riancho et al, 2020). Although it has been shown that TDP-43 is recruited less efficiently to DNA damage foci leading to unresolved DDR (Mitra et al, 2019), further studies are needed to examine DDR signalling pathways in ALS MDMi.…”
Section: Discussionsupporting
confidence: 93%
“…Given that TDP-43 mislocalisation is involved in the accumulation of DNA damage (Konopka et al, 2020), we evaluated DNA damage in ALS MDMi using an antibody recognising phosphorylated H2AX (γH2AX), which labels DNA double-strand breaks (DSBs). We found significantly increased γH2AX foci positive cells in ALS (30%) compared to HC MDMi (4%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ultimately it is imperative to elucidate the primary, upstream mechanisms responsible for neurodegeneration in ALS so that effective therapeutics can be designed. These mechanisms include impaired axonal transport (Collard et al, 1995 ; Williamson and Cleveland, 1999 ), neurofilament aggregation (Al-Chalabi et al, 1995 ; Xiao et al, 2006 ; Xu Z. et al, 2016 ), protein misfolding (Kopito, 2000 ; Basso et al, 2006 ), abnormal RNA processing (Chen et al, 2010 ; Dejesus-Hernandez et al, 2011 ; Parisi et al, 2013 ; Droppelmann et al, 2014 ), lipid peroxidation (Shibata et al, 2001 ) and cholesterol esterification (Cutler et al, 2002 ; Chaves-Filho et al, 2019 ), defects in nucleocytoplasmic transport (Boeynaems et al, 2016 ), induction of DNA damage (Konopka and Atkin, 2018 ; Naumann et al, 2018 ; Konopka et al, 2020 ), cytoplasmic mislocalization of nuclear proteins (Neumann et al, 2006 ), mitochondrial dysfunction (Albers and Beal, 2000 ), glutamate excitotoxicity (Shaw and Ince, 1997 ), proteasomal and autophagic dysfunction (Chen et al, 2012 ), ER stress (Nagata et al, 2007 ; Walker et al, 2010 ), mitochondrial associated membrane (MAM) dysfunction (Watanabe et al, 2016 ), ER-Golgi transport defects (Atkin et al, 2014 ; Soo et al, 2015 ), autophagy dysregulation and apoptosis (Ravits et al, 2013 ; Robberecht and Philips, 2013 ; Gao et al, 2017 ; Mandrioli et al, 2020 ). For a detailed discussion of these mechanisms, please see several excellent reviews (Zarei et al, 2015 ; Taylor et al, 2016 ; Weishaupt et al, 2016 ; Mejzini et al, 2019 ).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…This implies the presence of defects in DNA nick ligation and oxidative damage, and DNA repair mechanisms in FUS-associated ALS (Wang H. et al, 2018 ). Recently, TDP-43 was also shown to have a role in DNA repair (Mitra et al, 2019 ; Konopka et al, 2020 ), which is linked to oxidative stress (Guerrero et al, 2019 ). Collectively, these studies suggest that defects in DNA damage are a component of dysregulated redox homeostasis in ALS.…”
Section: Direct Evidence For a Role Of Redox Dysregulation In Alsmentioning
confidence: 99%